Positive influence of hippotherapy on the process of improvement of children with cerebral palsy in children - Oliwia Cywińska; Szymon Gawrych; Aleksandra Białkowska; Blanka Budziejko; Dariusz Dziarkowski; Daria Kurtyka; Gracjan Różański; Anna Maria Dobosiewicz; Nataliia Badiuk (Kazimierz Wielki University, 2018)
Cerebral palsy is one of the most common neurological diseases in children. An important aspect of improvement is the development of motor functions, self-service, communication and social skills. Therefore, rehabilitation, in all forms one of them is hippotherapy, must be focused on motor education, as well as on improving the child's psyche. The beneficial effect of a horse is that it controls muscle tension, strengthens flaccid muscles and relaxes shortened muscles, which prevents contractures. Therapeutic riding improves the quality of life of such children, allows them to open up to the world, thus activating them and creating interaction between the child and the horse, and this improves their physical and mental condition. Hippotherapy is one of the most effective complementary therapeutic methods used to improve children with cerebral palsy.